Exploring Dietary Behavior in At-Risk Youth Participating in an After-school Agricultural Program. Issue 6 (1st November 2020) - Cuy Castellanos, Diana; Holcomb, Jeanne; Fernando, Felix; Schneider, Kellie; McCullough, Deborah
ABSTRACT: Developing strategies to promote adequate dietary intake in children experiencing toxic stress could potentially reduce the cognitive impact on the brain and promote physical and mental health. The purpose of this research was to explore the impact of an afterschool agricultural and nutrition program on dietary behavior in 18 at-risk youth. We examined dietary intake and used Photovoice and semi-structured interviews to explore factors relating to dietary behavior. Results indicated higher intakes of fruit, vegetables and milk compared to a national sample. Further, the youth participants discussed the impact of the program on their dietary behavior through key socio-environmental and cognitive factors.